ARTIFICIAL INTELLIGENCE: REVOLUTIONARY APPROACHES AND THE SECRETS OF EFFICIENCY IN FOREIGN LANGUAGE TEACHING - M.B. Mirzaraimova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article investigates the transformative influence of Artificial Intelligence (AI) on foreign language pedagogy, focusing on its methodological innovations, adaptive learning potential, and assessment automation. Through the integration of natural language processing, speech recognition, and intelligent tutoring systems, AI has redefined traditional teaching frameworks. This article explores how AI fosters personalized learning, enhances pronunciation, and promotes learner autonomy. The article argues that AI not only increases efficiency and engagement in language learning but also contributes to the evolution of communicative competence in the digital era.